The efforts of Melayu Berbudaya community in promoting mechanical solidarity among its members - Suriyanisa, Suriyanisa; Imran, Imran; Ramadhan, Iwan; Sikwan, Agus; Hidayah, Riama Al; Hardiansyah, Muhammad Agus (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
The purpose of this study is to describe the efforts of Melayu Berbudaya Community in promoting mechanical solidarity among its members in South Pontianak District. The approach to this research is descriptive qualitative research. The results of the study showed that there are efforts among the members of Melayu Berbudaya Community in promoting mechanical solidarity in the low division of labor, strong collective awareness and low individuality among members. These things were promoted well because the members tried to maximize it in various ways. They were taking time to gather inside and outside their activities, contributing to each other, understanding each other and considering each other as family members. In addition, the goals of the members can be done because there are same purposes among them. Members of Melayu Berbudaya Community have strong mechanical solidarity, in which each member always creates togetherness and familiarity among members and works together to help people who need the help of Melayu Berbudaya Community.